Reduced α4 subunit expression in α4+− and α4+−/β2+− nicotinic acetylcholine receptors alters α4β2 subtype up‐regulation following chronic nicotine treatment. (1st August 2017) - Moretti, Milena; Fasoli, Francesca; Gotti, Cecilia; Marks, Michael J
Abstract : Background and Purpose: Genomic analysis has shown many variants in both CHRNA4 and CHRNB2, genes which encode the α4 and β2 subunits of nicotinic ACh receptors (nAChR) respectively. Some variants influence receptor expression, raising the possibility that CHRNA4 variants may affect response to tobacco use in humans. Chronic exposure to nicotine increases expression of nAChRs, particularly α4β2‐nAChRs, in humans and laboratory animals. Here, we have evaluated whether the initial level of receptor expression affects the increase in expression. Experimental Approach: Mice differing in expression of α4 and/or β2 nAChR subunits were chronically treated with saline, 0.25, 1.0 or 4.0 mg·kg −1 ·h −1 nicotine. Brain preparations were analysed autoradiographically by [ 125 I]‐epibatidine binding, immunoprecipitation and Western blotting. Key Results: Immunochemical studies confirmed that most of the [ 3 H]‐epibatidine binding corresponds to α4β2*‐nAChR and that increases in binding correspond to increases in α4 and β2 proteins. Consistent with previous reports, the dose‐dependent increase in nAChR in wild‐type mice following chronic nicotine treatment, measured with any of the methods, reached a maximum. Although receptor expression was reduced by approximately 50% in β2 +− mice, the pattern of response to chronic treatment resembled that of wild‐type mice. In contrast, both α4 +− and α4 +− /β2 +− exhibited relatively greater up‐regulation. Consistent with previous reports, α4β2α5‐nAChR did not increase in response to nicotine. Conclusions and Implications: These results indicate that mice with reduced expression of the α4 nAChR subunit have a more robust response to chronic nicotine than mice with normal expression of this subunit. Linked Articles: This article is part of a themed section on Nicotinic Acetylcholine Receptors. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v175.11/issuetoc